2019
DOI: 10.3390/cells8080859
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Obesity and Related Metabolic Disorders

Abstract: Metabolic disorders are characterized by the inability to properly use and/or store energy. The burdens of metabolic disease, such as obesity or diabetes, are believed to arise through a complex interplay between genetics and epigenetics predisposition, environment and nutrition. Therefore, understanding the molecular mechanisms for the onset of metabolic disease will provide new insights for prevention and treatment. There is growing concern about the dysregulation of micro-RNAs (miRNAs) in metabolic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 111 publications
1
155
0
3
Order By: Relevance
“…Recent studies have strongly implicated the microRNA system in regulating adipose tissue size and function [14][15][16]. For example, conditional deletion of Dicer from adipocytes inhibits lipogenesis in white adipocytes and produces severe depletion of white adipose tissue [17,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have strongly implicated the microRNA system in regulating adipose tissue size and function [14][15][16]. For example, conditional deletion of Dicer from adipocytes inhibits lipogenesis in white adipocytes and produces severe depletion of white adipose tissue [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Mice homozygous for the Tsnax (E126A) mutation display a metabolic profile that closely mimics that of Tsn KO mice.Selective deletion of Tsn or Tsnax from either adipocytes or hepatocytes, two candidate cell types, does not phenocopy the elevated adiposity displayed by mice with constitutive Tsn deletion or the Tsnax(E126A) mutation. Furthermore, global, conditional deletion of Tsn in adulthood does not elicit increased adiposity.Conclusion: Taken together, these findings indicate that inactivation of the TN/TX microRNA-degrading enzyme during development is necessary to drive the robust adiposity displayed by Tsn KO mice.Recent studies have strongly implicated the microRNA system in regulating adipose tissue size and function [14][15][16]. For example, conditional deletion of Dicer from adipocytes inhibits lipogenesis in white adipocytes and produces severe depletion of white adipose tissue [17,18].…”
mentioning
confidence: 99%
“…MiRNAs such as miR-17-5p, miR-132 and miR-21 result to be differentially regulated in white adipose tissue of obese subjects compared to lean subjects. [45,46]. MiRNAs modulation has also been correlated with anthropometric parameters (e.g., BMI, glycaemia, insulin levels) [47]; it has also been found that specific miRNAs are downregulated in WAT of obese patients [48].…”
Section: Epigenetics and Adipogenesismentioning
confidence: 97%
“…Obesity is a multifactorial disease, and over 30% of the population worldwide is nowadays considered overweight or obese [114]. Calorie intake, lifestyle, and genetic predisposition are all factors involved in the development of obesity, and the altered equilibrium between energy intake and consumption may lead to abnormal white fat accumulation [115]. Low-Density Lipoproteins (LDL) and High-Density Lipoproteins (HDL) contribute to lipid and cholesterol metabolism, and their production can be regulated by miRNAs.…”
Section: Mirna: a Factor In Multifactorial Diseasesmentioning
confidence: 99%